Pengaruh model anyaman serat kulit pohon waru (Hibiscus Tiliceus) terhadap kekuatan tarik komposit - Arief Rizki Fadhillah; Nova Risdiyanto Ismail; Dadang Hermawan; Renada Julia Sakinah (Universitas Muhammadiyah Metro, 2022)
Waru tree bark fiber (hibiscus tiliceus) has potential as a natural fiber composite reinforcement, but further research is needed by focusing on the woven fiber model on the strength of the waru tree bark composite material. The problem to be studied is